MANAJEMEN PEMBELAJARAN BERBASIS PROYEK PADA MATA KULIAH MANAJEMEN PERPUSTAKAAN - Sopwandin, Iwan; Nurhakim, Nova (STIT AL MULTAZAM, 2023)
Project-based learning is one approach that can be used to achieve students understanding of library management courses comprehensively, not only theoretically but also practically. This research describes the project-based learning management process in the library management course of the Islamic Education Management study program at the Tarbiyah Az Zahra Tasikmalaya College of Science. This research uses qualitative methods with data collection techniques consisting of observation, interviews and documentation studies. While data analysis techniques include data condensation, data presentation, and drawing conclusions. The results of the research show the project-based learning implementation is carried out with the following steps: 1) determining the project, activities in this stage include delivering the syllabus and identifying the form of the project according to student needs; 2) planning for project completion, in this stage a table is prepared, library processing practices are carried out, and student groups are divided; 3) project implementation is carried out after the lecture completes 8 class meetings; 4) monitoring project completion, this activity is carried out when students practice directly in the library and monitor the library management practice table; 5) assessment of project results, assessment is based on several things, including: a) student persistence in attending lectures (theoretical discussions) in class, b) filling in the logbook table, c) filling in the library management progress table; and d) the role or status of student activity; 6) evaluation and reflection on project results, each group creates and collects videos and slides about ongoing management practices and then presents them, after which it continues with reflection guided by the lecturer who teaches the library management course.